Uji aktivitas penghambatan enzim alfa amilase ekstrak dan fraksi daun binahong merah (anredera cordifolia (ten.) Steenis) - Normaita Latiefah Dinnar (CV. Publikasi Indonesia, 2022)
Diabetes mellitus (DM) is a chronic metabolic disorder, characterized by high levels of glucose in the blood (hyperglycemia) caused by decreased insulin secretion. One way to treat diabetes mellitus is to reduce postprandial glucose levels, which is to slow down glucose absorption through the inhibition of the alpha amylase enzyme. Alpha amylase inhibitors are compounds that can inhibit the breakdown of carbohydrates into glucose by the enzyme alpha amylase. One of the plants that have a hyperglycemic effect is red binahong (Anredera cordifolia (Ten.) Steenis). This study aimed to determine the inhibitory activity of the alpha amylase enzyme by ethanol extract and n-hexane, ethyl acetate, and ethanol-water fractions from the leaves of red binahong (Anredera cordifolia (Ten.) Steenis) in vitro with a standard inhibitor of acarbose as a comparison. Acarbose can delay the hydrolysis of carbohydrates and disaccharides, absorption of sugar and inhibit the metabolism of sucrose into glucose and fructose. From the results of the tests that have been carried out, it is known that the leaves of red binahong (Anredera cordifolia (Ten.) Steenis) contain secondary metabolites including flavonoids, alkaloids, tannins, and steroids/triterpenoids. Meanwhile, the results of the alpha amylase inhibition test by ethanol extract and fractions obtained IC50 values ​​of 113.926 mg/mL, 159.042 mg/mL, 23,609 mg/mL, and 31.704 mg/mL. Based on these results, it can be concluded that the ethyl acetate fraction of red binahong leaves (Anredera cordifolia (Ten.) Steenis) at a concentration of 200 ppm had the highest activity in inhibiting the alpha amylase enzyme with a percentage of inhibition of 84.650% and IC50 of 23.609 mg/mL.